2004
DOI: 10.1038/sj.cgt.7700676
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic antitumor effect by coexpression of chemokine CCL21/SLC and costimulatory molecule LIGHT

Abstract: To establish a more efficient treatment for immunotherapy against solid tumors, we have evaluated the antitumor effect by coexpression of a chemokine CCL21/secondary lymphoid tissue chemokine and a costimulatory molecule LIGHT in colon carcinoma C26. C26 cells expressing either CCL21 or LIGHT exhibited a significantly reduced tumor growth in vivo, and mice inoculated with these cells showed a prolonged survival, but eventually all these mice died. In contrast, C26 cells expressing both CCL21 and LIGHT exhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 45 publications
0
17
1
Order By: Relevance
“…The involvement of T lymphocytes in CCL21-mediated tumor targeting has previously been shown (4,5). However, in contrast to previous findings, when B16F0-UB-CCL21 cells were used for tumor inoculation, melanomas were heavily infiltrated with CD4 + CD25…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…The involvement of T lymphocytes in CCL21-mediated tumor targeting has previously been shown (4,5). However, in contrast to previous findings, when B16F0-UB-CCL21 cells were used for tumor inoculation, melanomas were heavily infiltrated with CD4 + CD25…”
Section: Discussioncontrasting
confidence: 53%
“…It has thus been suggested that this chemokine may promote recruitment of APC and T lymphocytes to a tumor mass to facilitate antigen recognition and enhance tumorspecific immune responses. In support of this concept, it was recently shown that the presence of CCL21 in the vicinity of a tumor induces infiltration of tumors with dendritic cell and CD8 + T cell and leads to immunemediated inhibition of melanoma (3), lung (4), and colon (5) carcinomas in experimental animals. Splenocytes isolated from these CCL21-treated mice showed greatly enhanced CTL activity against tumor cells (5).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…They reasoned that the observed enhancement in CTL activity and IFN-c production was mainly due to the efficient infiltration of the tumor by these immune cells. 32 Previous findings have also demonstrated that in situ expression of LIGHT could promote increased infiltration by CD8…”
Section: Discussionmentioning
confidence: 99%
“…Tumor volumes were calculated according to the formula: tumor volume = 0.5 (width 2 x length). 23 For the in vivo tumor treatment experiments using a lung metastasis model, mice (eight mice per group) were challenged with 1 x 10 5 TC-1 cells/mouse via tail vein (day 0). On day 7, mice were vaccinated with 1.25 µg of pSLC-E7-Fc, pE7-Fc and pCMV respectively and killed on day 21.…”
Section: Introductionmentioning
confidence: 99%